Using specialized software systems based on distributed storage airlines Ukraine - Иванкевич, А. В. (Problems of Informatization and Control, 2008)
The ways of implementation of balancing the distribution of information files on the network nodes in the processing of large amounts of data in information systems , which are used in aviation enterprises of Ukraine. The features of the work systems of distributed systems and the prospects for airlines to increase the performance of computer networks , based on which systems work